The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/ijwh.s376244
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Hyperandrogenism Include Hirsutism, Polycystic Ovary Syndrome, and Acne: Association with Psychiatric Disease in Women -A Nationwide Population-Based Cohort Study in Taiwan

Abstract: Objective Previous studies have shown an increased in psychiatric disorders in women with disorders associated with hyperandrogenism, but few nationwide cohorts have studied this phenomenon. Therefore, this study is aimed to examine the association between the clinical manifestations of hyperandrogenism and subsequent psychiatric disorders. Methods Based on the National Health Insurance Research Database, 49,770 enrolled participants were matched for age and index date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…A study has presented that women with hyperandrogenism, especially those aged 20-29, have an increased risk of developing psychiatric disorders. [28] Although the plasma androgen levels of our patients are normal for the diagnosis of idiopathic hirsutism, we found that the general health and mental health scores from the SF-36 questionnaire domains were low, and the BDI and BAI scores were high in the IH group. These findings suggest that the presence of hirsutism may affect HQOL, BDI, and BAI scores regardless of plasma androgen levels.…”
Section: Discussioncontrasting
confidence: 61%
“…A study has presented that women with hyperandrogenism, especially those aged 20-29, have an increased risk of developing psychiatric disorders. [28] Although the plasma androgen levels of our patients are normal for the diagnosis of idiopathic hirsutism, we found that the general health and mental health scores from the SF-36 questionnaire domains were low, and the BDI and BAI scores were high in the IH group. These findings suggest that the presence of hirsutism may affect HQOL, BDI, and BAI scores regardless of plasma androgen levels.…”
Section: Discussioncontrasting
confidence: 61%
“…Research indicates that the incidence of depression in individuals with PCOS ranges from 34 to 64%, and this rate shows an increasing trend over the years. Among them, reproductive-age women, particularly those between 20 and 35 years old, face a more significant risk of developing mental disorders (27). Reproductive-age women may experience a higher incidence of depression, possibly due to pressures related to childbirth, social and work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, testosterone (which is peripherally converted to dihydrotestosterone) is considered the most important androgen in hyperandrogenism, (Sharma and Welt, 2021). In females, excessive androgen levels disrupt the hypothalamic-pituitary-gonadal axis inducing reproductive dysfunction; and presenting with clinical features that include acne, hirsuitism, obesity, amenorrhea and/or hypomenorrhea (Wang et al, 2022). In the brain, there have been reports that androgens play crucial roles in the organisation, reorganisation and programming of the circuitry (Rubinow and Schmidt, 1996;Ambar and Chiavegatto, 2009;Costine et al, 2010;Onakomaiya et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…It Over the last several decades there have been reports on the neurobiological, neurobehavioural, neurochemical and neuromorphological effects of excess androgen levels on the brain (Rubinow and Schmidt, 1996;Ambar and Chiavegatto, 2009;. While the psychological and behavioural impact of excessive exogenous anabolic androgenic steroid administration and increased endogenous androgen levels in males has been the subject of investigation in the last several decades (Bahrke and Yesalis, 1990; Ambar and Chiavegatto, 2009), it is only in the last decade or more that associations have begun to be made between hyperandrogenism and the development of psychiatric illness in females (Costine et al, 2009;Wang et al, 2022). Wang et al (2022) reported that using the Cox proportional analysis to compare the risk of psychiatric disorders in a cohort of women with clinical features of hyperandrogenism during a 16 year follow-up period; they observed an increased risk of psychiatric illness particularly in those aged between 20 and 29 years (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%